2016
DOI: 10.1097/ta.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of shock in a nonhuman primate model of uncontrolled hemorrhage

Abstract: Acute alterations in StO2 and ETCO2 strongly associated with mortality and preceded those of traditional vital signs. The continuous, noninvasive aspects of Food and Drug Administration-approved StO2 and ETCO2 monitoring devices provide logistical benefits over other methodologies and thus warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…In animal studies, a statistically linear correlation was found between ETCO 2 which measured from the endotracheal tube and partial CO2 in the blood gas [ 9 ]. In another study, it was stated that tissue oxygen saturation and ETCO 2 values are good indicators of acute-phase shock [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, a statistically linear correlation was found between ETCO 2 which measured from the endotracheal tube and partial CO2 in the blood gas [ 9 ]. In another study, it was stated that tissue oxygen saturation and ETCO 2 values are good indicators of acute-phase shock [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crossland et al performed 60% left hepatectomy in 16 rhesus monkeys to induce hemorrhage and found that there was a significant difference in ETCO 2 between survivors and nonsurvivors at 5 min after resection, indicating that ETCO 2 is an effective predictor of patient outcomes (37). Campion et al also reached the same conclusion after reviewing the ETCO 2 values of 173 trauma patients before discharge (35).…”
Section: End-tidal Carbon Dioxidementioning
confidence: 99%